2013
DOI: 10.26418/j.sea.v1i1.2118
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Bisnis Sosial Pedagang Perantara Dalam Upaya Pengembangan Hortikultura Di Jawa Barat

Abstract: Currently, 90% of Indonesian small scale agribusiness actors arebeing faced to the global market era. They are also facing a fast growthrate of global market and the market segmentation phenomenon whichexpects positive changes and adaptations in the agricultural supply chain.The method that used in this study is case study. The study location wasbeing selected based on its potential of horticulture product.The study showed that currently the traders have changed theirbusiness pattern from a pure business to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Therefore, middlemen's functions and duties must be clarified to accelerate shallot farming's turnover of funds. Research results from Charina et al (2012) showed that middlemen can be categorized as semi-social businesses by establishing partnerships with farmers due to the ever-increasing consumer demand for a commodity.…”
Section: Evenmentioning
confidence: 99%
“…Therefore, middlemen's functions and duties must be clarified to accelerate shallot farming's turnover of funds. Research results from Charina et al (2012) showed that middlemen can be categorized as semi-social businesses by establishing partnerships with farmers due to the ever-increasing consumer demand for a commodity.…”
Section: Evenmentioning
confidence: 99%
“…Hal ini menyebabkan masyarakat sebagai produsen memperoleh keuntungan yang lebih kecil dibanding para pedagang perantara atau broker (Charina, Mukti, & Andriani, 2012). 2.…”
Section: Tersedia Tempat Penyulingan Minyak Masoiunclassified